Analisis Penerapan Rme Berbantuan Geogebra Untuk Meningkatkan Hasil Belajar Siswa Dengan Uji Paired Sample T-Test - Novita Sari Maria; Siti Khafifah F; Afta Geosasmita Saragih; Aini Wardana; Prihatin Ningsih Sagala; Ruth Sahanaya Manik (CV. Ulil Albab Corp, 2025)
This study aims to analyze the effectiveness of the Realistic Mathematics Education (RME) approach supported by GeoGebra software in improving students' learning outcomes. The research method employed is pre-experimental with a one-group pretest-posttest design. The research sample consisted of 27 students from class IX-7 at SMPN 27 Medan, who participated in mathematics learning using the RME approach assisted by GeoGebra. Data collection was conducted through learning outcome tests, which were then analyzed using the Shapiro-Wilk normality test and the paired sample t-test. The analysis results indicate that the pretest and posttest data are normally distributed, with the t-test yielding a t-value of -9.0872 and a p-value of 1.496e-09, demonstrating a significant improvement in learning outcomes after implementing the RME approach with GeoGebra. The average difference between pretest and posttest scores was -20.25926, with a 95% confidence interval (-24.84191 to -15.67660). These findings confirm that the RME approach supported by GeoGebra is effective in enhancing students' mathematical understanding and skills.